Vertical Stability Study for Dams in Latakia Case Study - 16 Tishreen Dam and the Althawra Dam - احمد محسن; فحصة اياد; الحسن علي (Latakia University Journal -Engineering Sciences Series, 2021)
Our research aim to study the elevation stability of the two largest dams of Latakia (16 Tishreen dam and Althawra dam) during the period from their construction until the eleventh month of 2020, by conducting three approval measurement cycles of the dam life cycle which are partial fullness, full fullness and severe discharge each year, The results were compared between the three cycles and between them and the initial state of the altimetric Observation Network at the start of the dam investment, through the altimeter observation points preserved until the time of our study. The results of the measurements showed that the elevation control points were stable during the three measurement cycles approved for the annual life cycle of each of the two dams studied in 2020, The study of stability over the period between the dam’s construction and the present time has shown that: The control points on the concrete installations were stable and there was no vertical displacement 2- The elevation control points on the terraces of the 16 Tishreen dam fell a maximum of 7 cm The altitude control points on the terraces of the revolution dam could have fallen by an average of 13 cm.